2014
DOI: 10.1002/jps.23978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ball-Milling and Cryomilling on Sulfamerazine Polymorphs: A Quantitative Study

Abstract: The effects of ball-milling and cryomilling on sulfamerazine forms I and II (SMZ FI, FII) were investigated using X-ray powder diffraction, IR and NIR spectroscopy. Cryomilling resulted in the complete amorphization of both polymorphs. Milling at room temperature gave mixtures of amorphous SMZ (FA) and FII. Calibration models were developed for the quantitative analysis of binary (FI/FII, FI/FA and FII/FA) and ternary (FI/FII/FA) mixtures using NIR spectroscopy combined with partial least-squares (PLS) regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 84 publications
1
39
0
Order By: Relevance
“…Cryomilling holds the sample at a temperature below 0 o C, which helps to prevent crystallization of the sample during milling. 48 As shown in Figure 4, following cryomilling CIP still had some residual crystallinity. The four most prominent peaks of the CIP zwitterion are still present in the PXRD of the cryomilled sample; however they are less intense than those obtained with the drug milled at room temperature.…”
Section: Cryomillingmentioning
confidence: 94%
“…Cryomilling holds the sample at a temperature below 0 o C, which helps to prevent crystallization of the sample during milling. 48 As shown in Figure 4, following cryomilling CIP still had some residual crystallinity. The four most prominent peaks of the CIP zwitterion are still present in the PXRD of the cryomilled sample; however they are less intense than those obtained with the drug milled at room temperature.…”
Section: Cryomillingmentioning
confidence: 94%
“…Co-amorphous SMZ/CA was prepared by cryomilling an equimolar mixture of SMZ and CA and characterized by XRPD as previously described by us (MacFhionnghaile et al, 2014). Co-amorphous SMZ/DA and SMZ/NaTC were obtained in the same way in the present study.…”
Section: Preparation and Characterization Of The Co-amorphous Systemsmentioning
confidence: 99%
“…We have recently studied the milling-induced amorphization of the model API sulfamerazine (SMZ) and demonstrated that co-milling with multifunctional carboxylic acids such as citric acid (CA) can increase the stability of the amorphous phase under ambient conditions from a few hours for the drug alone to several weeks (MacFhionnghaile et al, 2014). In continuation of this work we now report a detailed study of the dissolution behavior of three selected co-amorphous SMZ/carboxylic acid co-former systems, namely SMZ/DA, SMZ/CA and SMZ/NaTC (DA = deoxycholic acid, NaTC = sodium taurocholate, Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanochemistry, due to its non-equilibrium nature, is often employed to produce polymorphs 6 and co-crystals 53 Co-milled 1 and g (HP) in a 1:1 ratio results in a new XRPD pattern ( Figure S13, SI) suggesting the formation of a new co-crystalline adduct. This is further supported by the thermal analysis ( Figure S14, SI) where the material shows an endothermic peak at 187 °C, followed by melting at 202 °C.…”
Section: Ball Millingmentioning
confidence: 99%